On Trace Regularity of Solutions to a Wave Equation with Homogeneous Neumann Boundary Conditions - Ryzhkova, I. A. (Журнал математичної фізики, аналізу, геометрії, 2007)
We prove an additional regularity of time derivative of the trace of solution to the wave equation on the 3D half space with the homogeneous Neumann boundary conditions. Mathematics Subject Classification: 35L05, 35B65.